Anatase TiO2 as a Cheap and Sustainable Buffering Filler for Silicon Nanoparticles in Lithium‐Ion Battery Anodes. Issue 23 (2nd November 2017) - Maroni, Fabio; Carbonari, Gilberto; Croce, Fausto; Tossici, Roberto; Nobili, Francesco
Abstract: The design of effective supporting matrices to efficiently cycle Si nanoparticles is often difficult to achieve and requires complex preparation strategies. In this work, we present a simple synthesis of low‐cost and environmentally benign aAnatase TiO2 nanoparticles as buffering filler for Si nanoparticles (Si@TiO2 ). The average anatase TiO2 crystallite size was approximately 5 nm. A complete structural, morphological, and electrochemical characterization was performed. Electrochemical test results show very good specific capacity values of up to 1000 mAh g −1 and cycling at several specific currents, ranging from 500 to 2000 mA g −1, demonstrating a very good tolerance to high cycling rates. Postmortem morphological analysis shows very good electrode integrity after 100 cycles at 500 mA g −1 specific current. Abstract : High rates, with low polarization : Low‐cost and environmentally benign anatase TiO2 nanoparticles were used as a buffering filler for Si nanoparticles. The average anatase TiO2 crystallite size was approximately 5 nm. Electrochemical tests showed very good specific capacity values of up to 1000 mAh g −1 and cycling at several specific currents from 500 mA g −1 to 2000 mA g −1, demonstrating a very good tolerance to high cycling rates.